Analisis terhadap Unsur-Unsur Perbuatan Melawan Hukum dalam Putusan Pengadilan Negeri Jakarta Selatan Nomor 79/Pdt.G/2023/PN Jkt.Sel Tahun 2023 - Aisyah Febria Hendri; Rahma Tazkia; Zalfa Zinan; Sulastri S (Media Hukum Indonesia (MHI), 2026)
This research analyzes the elements of illegal acts (PMH) in the South Jakarta District Court Decision Number 79/Pdt.G/2023/PN Jkt.Sel Year 2023. The method used is juridical normative through the examination of the decision as a primary source, as well as the analysis of Article 1365 of the Civil Code, the ITE Law, and the Telecommunication Law as a normative framework. The research results show that the panel of judges stated that the lawsuit was unacceptable because it was considered premature, so that the elements of PMH could not be tested substantially. This decision emphasizes the importance of the relationship between the criminal proof process and civil proof in PMH cases related to alleged telecommunication violations.